Bilateral Globus Pallidus Internus Deep Brain Stimulation in a Case of Progressive Dystonia in Mohr-Tranebjaerg Syndrome with Bilateral Cochlear Implants - Coenen, Volker Arnd; Rijntjes, Michel; Sajonz, Bastian; Piroth, Tobias; Prokop, Thomas; Jost, Wolfgang; Trippel, Michael; Urbach, Horst; Reinacher, Peter Christoph (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Introduction A 28-year-old man presented with a history of sensorineural deafness since early childhood treated with bilateral cochlear implants (CIs). He showed signs of debilitating dystonia that had been present since puberty. Dystonic symptoms, especially a protrusion of the tongue and bilateral hand tremor, had not responded to botulinum toxin therapy. We diagnosed Mohr-Tranebjaerg syndrome (MTS).Methods and Material Deep brain stimulation (DBS) of the bilateral globus pallidus internus was performed predominantly with stereotaxic computed tomography angiography guidance under general anesthesia. Electrophysiology was used to identify the target regions and to guide DBS electrode placement.Results In the immediate postoperative course and stimulation, the patient showed marked improvement of facial, extremity, and cervical dystonia. More than 2 years after implantation, his dystonic symptoms had dramatically improved by 82%.Discussion MTS is a rare genetic disorder leading to sensorineural deafness, dystonia, and other symptoms. The use of DBS for the dystonia in MTS was previously described but not in the presence of bilateral CIs.Conclusion DBS in MTS may be a viable option to treat debilitating dystonic symptoms. We describe successful DBS surgery, despite the presence of bilateral CIs, and stimulation therapy over 2 years.
Keywords: cochlear implant; deafness dystonia; deep brain stimulation; Mohr-Tranebjaerg syndrome